Telemonitoring and/or self-monitoring of blood pressure in hypertension (TASMINH4): protocol for a randomised controlled trial. Issue 1 (December 2017) - Franssen, Marloes; Farmer, Andrew; Grant, Sabrina; Greenfield, Sheila; Heneghan, Carl; Hobbs, Richard; Hodgkinson, James; Jowett, Susan; Mant, Jonathan; Martin, Una; Milner, Siobhan; Monahan, Mark; et al.
Abstract Background Self-monitoring of hypertension is associated with lower systolic blood pressure (SBP). However, evidence for the use of self-monitoring to titrate antihypertensive medication by physicians is equivocal. Furthermore, there is some evidence for the efficacy of telemonitoring in the management of hypertension but it is not clear what this adds over and above self-monitoring. This trial aims to evaluate whether GP led antihypertensive titration using self-monitoring results in lower SBP compared to usual care and whether telemonitoring adds anything to self-monitoring alone. Methods/Design This will be a pragmatic primary care based, unblinded, randomised controlled trial of self-monitoring of BP with or without telemonitoring compared to usual care. Eligible patients will have poorly controlled hypertension (>140/90 mmHg) and will be recruited from primary care. Participants will be individually randomised to either usual care, self-monitoring alone, or self-monitoring with telemonitoring. The primary outcome of the trial will be difference in clinic SBP between intervention and control groups at 12 months adjusted for baseline SBP, gender, BP target and practice. At least 1110 patients will be sufficient to detect a difference in SBP between self-monitoring with or without telemonitoring and usual care of 5 mmHg with 90% power with an adjusted alpha of 0.017 (2-sided) to adjust for all three pairwise comparisons. Other outcomes will include adherence of anti-hypertensive medication, lifestyle behaviours, health-related quality of life, and adverse events. An economic analysis will consider both within trial costs and a model extrapolating the results thereafter. A qualitative sub study will gain insights into the views, experiences and decision making processes of patients and health care professionals focusing on the acceptability of self-monitoring and telemonitoring in the routine management of hypertension. Discussion The results of the trial will be directly applicable to primary care in the UK. If successful, self-monitoring of BP in people with hypertension would be applicable to hundreds of thousands of individuals in the UK. Trial registration ISRCTN 83571366 . Registered 17 July 2014